Pengembangan Media Flipbook Berbasis Augmented Reality Materi Kenampakan Alam untuk Meningkatkan Motivasi Belajar Siswa Kelas III Sekolah Dasar - Asasiatinnisa, Takhlishu; Kurnianto, Bagas (Paedagogie, 2026)
This study aims to develop Augmented Reality-based flipbook learning media for IPAS material and measure its effectiveness in increasing the learning motivation of third-grade elementary school students. The approach used is Research and Development (R&D) with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects were third-grade students at Gisikdrono 02 Public Elementary School. Data collection instruments included expert validation questionnaires, motivation questionnaires, teacher and student response questionnaires, observations, and pretest and posttest tests. The data obtained were then analyzed descriptively and statistically to see the increase in student learning motivation after the media was used. The results of the research revealed that the Augmented Reality-based flipbook media developed received a “very feasible” rating from subject matter experts and media experts. The implementation results showed that student learning motivation increased from 65% at the beginning to 88% after using the media, which indicates an increase in the learning motivation of third-grade students in IPAS learning. In addition, the pretest and posttest results and statistical tests also improved after using this AR Flipbook media. Based on the research findings, flipbook media integrated with Augmented Reality technology proved to be effective in encouraging learning motivation among third-grade elementary school students.